UNDERSTANDING OF SEX EDUCATION LITERACY: A CASE STUDY OF FOURTH AND FIFTH-GRADE STUDENTS AT AZZAHRO SCHOOL TANGERANG - Cahya Adhitya Pratama; Gery Erlangga; Herdin Muhtarom; Aditya Aditya; Puput Andriani; Suswandari Suswandari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Understanding sex education for children is crucial to understand as a provision to select the right healthy friendship with their friends. It is a reason why this paper is made to provide clear counseling so that the students of SDI Azzahro Tangerang understand sex education as a provision in socialization along with the increasing level of violence and sexual abuse against children. The purpose of the research was to analyze the understanding of sex education for 4th and 5th graders at SDI Azzahro Tangerang. The research uses a qualitative method with a descriptive phenomenological approach. The findings and results of the research indicate that after counseling about sex education, students have an understanding of sex education that can be applied in everyday life. The results can be recommended to teachers to provide teaching and learning materials consistently regarding sex education in order to obtain a further understanding for students.